Upconversion Nanoparticles for Bioimaging and Regenerative Medicine - González-Béjar, María; Francés-Soriano, Laura; Pérez-Prieto, Julia (Frontiers in Bioengineering and Biotechnology, 2016)
Nanomaterials are proving useful for regenerative medicine in combination with stem cell therapy. Nanoparticles can be administrated and targeted to desired tissues or organs and subsequently, be used in non-invasive real-time visualization and tracking of cells by means of different imaging techniques, they can act as therapeutic agent nanocarriers, and can also serve as scaffolds to guide the growth of new tissue. Nanoparticles can be of different chemical nature, such as gold, iron oxide, cadmium selenide, and carbon, and have the potential to be used in regenerative medicine. However, there are still many issues to be solved, such as toxicity, stability, and resident time. Upconversion nanoparticles have relevant properties such as: i) low toxicity, ii) capability to absorb light in an optical region where absorption in tissues is minimal and penetration is optimal (note they can also be designed to emit in the NIR region), and iii) they can be used in multiplexing and multimodal imaging. An overview on the potentiality of upconversion materials in regenerative medicine is given.